Cell‐free artificial implants of electrospun fibres in a three‐dimensional gelatin matrix support sciatic nerve regeneration in vivo. (27th January 2017) - Kriebel, Andreas; Hodde, Dorothee; Kuenzel, Thomas; Engels, Jessica; Brook, Gary; Mey, Jörg
Abstract: Surgical repair of larger peripheral nerve lesions requires the use of autologous nerve grafts. At present, clinical alternatives to avoid nerve transplantation consist of empty tubes, which are only suitable for the repair over short distances and have limited success. We developed a cell‐free, three‐dimensional scaffold for axonal guidance in long‐distance nerve repair. Sub‐micron scale fibres of biodegradable poly‐ε‐caprolactone (PCL) and collagen/PCL (c/PCL) blends were incorporated in a gelatin matrix and inserted in collagen tubes. The conduits were tested by replacing 15‐mm‐long segments of rat sciatic nerves in vivo . Biocompatibility of the implants and nerve regeneration were assessed histologically, with electromyography and with behavioural tests for motor functions. Functional repair was achieved in all animals with autologous transplants, in 12 of 13 rats that received artificial implants with an internal structure and in half of the animals with empty nerve conduits. In rats with implants containing c/PCL fibres, the extent of recovery (compound muscle action potentials, motor functions of the hind limbs) was superior to animals that had received empty implants, but not as good as with autologous nerve transplantation. Schwann cell migration and axonal regeneration were observed in all artificial implants, and muscular atrophy was reduced in comparison with animals that had received no implants. The present design represents a significant step towards cell‐free, artificial nerve bridges that can replace autologous nerve transplants in the clinic. Copyright © 2017 John Wiley & Sons, Ltd.